Corrosion Inhibition of Mild Steel in Acidic Medium Using High Altitude Plant Extract - Lama, Roshan; Das, Anju Kumari; Yadav, Brahamdeo; Chaudhary, Yogesh; Lama, Prakash Chandra; Shrestha, Suman Lal; Gupta, Dipak K.; Karki, Nabin; Yadav, Amar P. (Journal of Nepal Chemical Society, 2018)
Available with fulltext.